Social impacts of large dams: gender, equity and distribution issues - Srinivasan, Bina (2001)
The complexities of the imbalances between the `losers' and the `winners' in the distribution of the benefits of large dams are the main issues in formulating the parameters of equity principles. Gender is one layer in this complexity, and is one of the most basic aspects of a realistic impacts assessment. Gender is fundamental to equity and distribution. Due to the far-reaching transformations initiated by large dams, it is essential to ensure that the negative impacts do not outweight the positive ones. Therefore, an integration of gender is indispensable in any process that seeks to formulate equity principles. - Reproduced
Keywords: Women; Dams